2014
DOI: 10.1063/1.4898712
|View full text |Cite
|
Sign up to set email alerts
|

Does water dope carbon nanotubes?

Abstract: We calculate the long-range perturbation to the electronic charge density of carbon nanotubes (CNTs) as a result of the physisorption of a water molecule. We find that the dominant effect is a charge redistribution in the CNT due to polarisation caused by the dipole moment of the water molecule. The charge redistribution is found to occur over a length-scale greater than 30 Å, highlighting the need for large-scale simulations. By comparing our fully first-principles calculations to ones in which the perturbati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
1
20
1
Order By: Relevance
“…It has been previously reported that water induces n-type 65,66 or p-type 56,[67][68][69] responses from carbon nanotubes, causing a change in the conductance of ropes and bundles. The study by Bell et al 70 suggested that this effect is attributable to electrostatic interactions. The permanent dipole moment of water induces a polarisation of electronic charge density in the nanotube over a long range (3 nm).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that water induces n-type 65,66 or p-type 56,[67][68][69] responses from carbon nanotubes, causing a change in the conductance of ropes and bundles. The study by Bell et al 70 suggested that this effect is attributable to electrostatic interactions. The permanent dipole moment of water induces a polarisation of electronic charge density in the nanotube over a long range (3 nm).…”
Section: Resultsmentioning
confidence: 99%
“…6a). The sensitivity of carbon nanotubes to water vapour is well reported [66][67][68] . As the nanotubes contribute significantly towards conduction in the composites, any interactions inducing changes in conductance of the tubes, will have a large overall effect on the resistance of the sensor, which may have been the cause of the larger responses to water.…”
Section: Sensitivity To Water Vapourmentioning
confidence: 79%
“…This gives greater flexibility in the sense of allowing the study of inter-tube conductance between CNTs of different chiralities. This and a detailed analysis of inter-tube scattering in CNT networks will be provided elsewhere [56].…”
Section: Scattering At Cnt Endsmentioning
confidence: 99%